2017
DOI: 10.1016/j.wem.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Upper Body Compression Garment: Physiological Effects While Cycling in a Hot Environment

Abstract: The use of an UBCG increased cardiovascular and thermoregulatory strain during cycling in a hot environment and did not aid during recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…during exercise and/or recovery) [7][8][9], the garment pressure and distribution [10][11][12], where compression is applied (e.g. upper body [torso and/or arms] vs lower body [knee/thigh/full length]) [13,14], the level of competition at which the athlete/participant competes [12,15,16], the type of exercise performed [7,15], and the athlete's belief in the product [2,17]. Furthermore, considerations such as garment pressure have been estimated to be reported in only one third of the literature to date [6].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…during exercise and/or recovery) [7][8][9], the garment pressure and distribution [10][11][12], where compression is applied (e.g. upper body [torso and/or arms] vs lower body [knee/thigh/full length]) [13,14], the level of competition at which the athlete/participant competes [12,15,16], the type of exercise performed [7,15], and the athlete's belief in the product [2,17]. Furthermore, considerations such as garment pressure have been estimated to be reported in only one third of the literature to date [6].…”
Section: Study Selectionmentioning
confidence: 99%
“…It should be noted that if an outcome measure was assessed but was only used to describe participant characteristics rather than used as an outcome of the intervention (e.g. VO 2max of participants in each group [14,27]), it was not included in the corresponding table and section. The general characteristics (i.e.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, changes in skin temperature depend on the type of exercise, environmental conditions, and/or the type of garment and its properties. While studies with upper-body compression garments observed increases in core and skin temperature during aerobic exercise [ 29 ], studies with lower-body compression did not observe any apparent effect on skin and core temperature [ 30 ]. In addition, low transpiration of the textile could result in a higher increase in the skin temperature during exercise [ 31 ].…”
Section: Discussionmentioning
confidence: 99%